Differences in dorsal and ventral pigmentation result from regional expression of the mouse agouti gene. - Vrieling, H (1994)
The agouti coat color gene encodes a paracrine signaling molecule that controls the production of yellow and black pigment by melanocytes within hair follicles. Some agouti alleles affect the dorsum and ventrum independently, which has provided the basis for speculation that agouti gene action in different regions of the body is controlled by distinct genetic loci that are closely linked. Using a combination of cDNA cloning and RNA expression studies, we find that alternative isoforms of agouti mRNA contain different noncoding first exons located 100 kb apart, whose patterns of expression indicate independent control by regulatory elements that are either ventral specific or hair cycle specific. These results demonstrate that the apparent genetic complexity of the agouti locus is explained by the existence of multiple regulatory elements exerting control over a single coding sequence and provide a conceptual basis for understanding differences in dorsal and ventral hair coloration in many mammalian species. The ventral-specific agouti isoform represents an example of a transcript whose expression is restricted to ventral skin and provide an approach to investigate the mechanisms by which dorsal-ventral differences in gene expression are established and maintained.